2018
DOI: 10.1111/1462-2920.14099
|View full text |Cite
|
Sign up to set email alerts
|

Two novel decarboxylase genes play a key role in the stereospecific catabolism of dehydrodiconiferyl alcohol in Sphingobium sp. strain SYK‐6

Abstract: Sphingobium sp. strain SYK-6 is able to use a phenylcoumaran-type biaryl, dehydrodiconiferyl alcohol (DCA), as a sole source of carbon and energy. In SYK-6 cells, the alcohol group of the B-ring side chain of DCA was first oxidized to the carboxyl group, and then the alcohol group of the A-ring side chain was oxidized to generate 5-(2-carboxyvinyl)-2-(4-hydroxy-3-methoxyphenyl)-7-methoxy-2,3-dihydrobenzofuran-3-carboxylate (DCA-CC). We identified phcF, phcG and phcH, which conferred the ability to convert DCA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…HPLC-based assays further revealed that the LSD4-catalyzed cleavage of DCA-S and lignostilbene yielded 1.1 ± 0.3 mol and 2.6 ± 0.2 mol vanillin per mol O 2 consumed, respectively. Overall, these analyses demonstrated that LSD4 catalyzes the cleavage of DCA-S to vanillin and 5-formylferulate, consistent with the proposed DCA catabolic pathway of SYK-6 ( 14 , 16 ), and that the cleavage of lignostilbene and DCA-S is well coupled to O 2 consumption.
Figure 4 LSD4-catalyzed DCA-S cleavage products.
…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…HPLC-based assays further revealed that the LSD4-catalyzed cleavage of DCA-S and lignostilbene yielded 1.1 ± 0.3 mol and 2.6 ± 0.2 mol vanillin per mol O 2 consumed, respectively. Overall, these analyses demonstrated that LSD4 catalyzes the cleavage of DCA-S to vanillin and 5-formylferulate, consistent with the proposed DCA catabolic pathway of SYK-6 ( 14 , 16 ), and that the cleavage of lignostilbene and DCA-S is well coupled to O 2 consumption.
Figure 4 LSD4-catalyzed DCA-S cleavage products.
…”
Section: Resultssupporting
confidence: 69%
“…By contrast, the enzymes that oxidize the methyl alcohol attached to the coumaran moiety of DCA-C have been partially characterized. PhcC, PhcD, and an unidentified dehydrogenase catalyze the oxidation of DCA-C to the two stereoisomers of 5-(2-carboxyvinyl)-2-(4-hydroxy-3-methoxy-phenyl)-7-methoxy-2,3-dihydrobenzofuran-3-carboxylate (DCA-CC) via an aldehyde intermediate, 3-(3-formyl-2-(4-hydroxy-3-methoxyphenyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl)acrylate (DCA-CL) ( 16 ). PhcC and PhcD are glucose-methanol-choline oxidoreductases, and their reactions are coupled to respiration ( 15 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lignostilbenoids occur in a very limited number of naturally occurring lignins but are prevalent in industrial lignins due to condensation reactions (10,11). Moreover, lignin-derived stilbenes are proposed to be produced in the bacterial catabolism of diaryl propane and phenylcoumarane (7,12). Plants produce other stilbenes, such as resveratrol, arachidins, and astringins, as allelochemicals to protect against pathogens and physical damage (13).…”
Section: Lignostilbene-␣␤-dioxygenase a (Lsda) From The Bacteriummentioning
confidence: 99%
“…Plants produce other stilbenes, such as resveratrol, arachidins, and astringins, as allelochemicals to protect against pathogens and physical damage (13). This variety of stilbenes may explain why some bacterial strains contain multiple LSD homologs (5,7,12,14,15). The first LSD to be described, LsdA from Sphingomonas paucimobilis TMY1009 (TMY1009 hereafter), shares 98% amino acid sequence identity with LSD1 from Sphingobium sp.…”
Section: Lignostilbene-␣␤-dioxygenase a (Lsda) From The Bacteriummentioning
confidence: 99%